The Correlation of Peer Conformity and Parents Support with Juvenile Delinquency - Aghnia Sadida; Herman Nirwana; Riska Ahmad (International Conferences on Educational, Social Sciences and Technology)
The purposes of this study are to test correlation peer conformity, parents support, juvenile delinquency, and the peer conformity, parental support, partially and simultaneously with the juvenile delinquency. The sample consisted of 115 people taken by using the stratified random sampling. The results show that there is correlation of peer conformity to juvenile delinquency was -0,235, the correlation of parents support to juvenile delinquency was -0,206 and the correlation of peer conformity and parents support to juvenile delinquency was -0,292.